ENGLISH EDUCATION STUDY PROGRAM STUDENTS’ PERCEPTIONS ON IMPROVING SPEAKING SKILLS THROUGH LITMATCH - Puspitasari, Indah; Sholeha, Ucik Intan (Premise: Journal of English Education and Applied Linguistics, 2025)
This study aims to determine students' perceptions of Litmatch in improving speaking skills. Data were obtained through speaking classes in Litmatch and also through an online survey shared via links on social media. This study utilizes quantitative descriptive research to understand the usage, influence, motivation, and perceptions of the sample. The respondents in this study were 27 students from the English Education Department at STKIP PGRI Pacitan. The sampling technique employed Litmatch and Google Form as media, resulting in summarized findings in the form of tables and diagrams. The research findings indicate that Litmatch application as easy to use and with simple navigation, where the majority of respondents chose "agree" with a total of 13 respondents (48.1%), provides features to practice speaking, where the majority of respondents chose "agree" with a total of 14 respondents (51.9%), improve speaking skill where the majority of respondents chose "agree" with a total of 16 respondents (59.3%), motivates users to practice speaking English more frequently where the majority of respondents chose "agree" with a total of 15 respondents (55.6%), and 22 respondents (81.5%) recommend Litmatch to other English Education students to improve their speaking skills.